2014
DOI: 10.1159/000362733
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Use of Glucocorticoids in Rheumatoid Arthritis

Abstract: A clear temporal relationship exists in rheumatoid arthritis (RA) patients between increased nocturnal levels of pro-inflammatory cytokines, such as TNF-α and interleukin (IL)-6, pro-inflammatory hormones (i.e. melatonin, prolactin) and insufficient night production of the anti-inflammatory cortisol (circadian rhythm). Under long-standing chronic stress of disease, insufficient cortisol is available to inhibit an ongoing nocturnal immune/inflammatory reaction. Clinical RA symptoms follow the same circadian rhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…All the investigations confirmed that the specific timing of exogenous prednisone availability, linked to the interaction between IL-6 and the HPA axis, may correct in RA a postulated deficiency regarding the HPA control [ 38 ].…”
Section: Low-dose Glucocorticoids and Chronotherapy In Rheumatoid Artmentioning
confidence: 81%
“…All the investigations confirmed that the specific timing of exogenous prednisone availability, linked to the interaction between IL-6 and the HPA axis, may correct in RA a postulated deficiency regarding the HPA control [ 38 ].…”
Section: Low-dose Glucocorticoids and Chronotherapy In Rheumatoid Artmentioning
confidence: 81%
“…The peak of inflammatory factor production occurs in association with low levels of cortisol. TNF-α and IL-6 production during active phases is consistent with reduction of night-time cortisol production [ 230 ]. Cortisol production is regulated by circadian rhythms that present an elevated morning level, but normalizes by the evening in MS patients [ 231 ].…”
Section: Circadian Rhythms In Msmentioning
confidence: 84%
“…A characteristic feature of RA is the change in disease activity over the day, measured by symptoms, and circulating markers of the inflammatory process such as IL-6 [31, 32]. Indeed, there have been attempts to add circadian logic to therapy, with modified release prednisolone tablets entering the clinic [33].…”
Section: Discussionmentioning
confidence: 99%